Intellectual Property Rights and Monopoly in the Perspective of Islamic Jurisprudence - Meirison, Meirison; Nazar, Zerly (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2021)
This paper aims to reveal fiqh's review of Intellectual Property Rights (IPR) and their relationship with monopolies that can harm humankind. There are two opinions in contemporary fiqh regarding IPR; first, Ahmad al-á¸¤ujjÄ« al-KurdÄ«, which states that IPR as part of worship, should not be hidden and should not be monopolized and exploited by anyone. Second, Muá¹£á¹afÄ ZarqÄ, Muá¸¥ammad Fatá¸¥Ä« al-DuraynÄ«, Muá¸¥ammad Sa'Ä«d Ramaá¸Än al-BÅ«á¹Ä« who agree with the protection of IPR. Through literature study and descriptive analysis approach, this paper concludes that if intellectual property rights cause harm to society and the state, especially in the exploitation of material rights, then it has created a monopoly that is detrimental and prohibited. Every country has different policies to protect IPR when it does not harm the community and the state.Â